Morphology and geology of the continental shelf and upper slope of southern Central Chile (33°S–43°S) - Völker, David; Geersen, Jacob; Contreras-Reyes, Eduardo; Sellanes, Javier; Pantoja, Silvio; Rabbel, Wolfgang; Thorwart, Martin; Reichert, Christian; Block, Martin; Weinrebe, Wilhelm Reimer (International journal of earth sciences : Geologische Rundschau, 2014)
The continental shelf and slope of southern Central Chile have been subject to a number of international as well as Chilean research campaigns over the last 30 years. This work summarizes the geologic setting of the southern Central Chilean Continental shelf (33°S–43°S) using recently published geophysical, seismological, sedimentological and bio-geochemical data. Additionally, unpublished data such as reflection seismic profiles, swath bathymetry and observations on biota that allow further insights into the evolution of this continental platform are integrated. The outcome is an overview of the current knowledge about the geology of the southern Central Chilean shelf and upper slope. We observe both patches of reduced as well as high recent sedimentation on the shelf and upper slope, due to local redistribution of fluvial input, mainly governed by bottom currents and submarine canyons and highly productive upwelling zones. Shelf basins show highly variable thickness of Oligocene-Quaternary sedimentary units that are dissected by the marine continuations of upper plate faults known from land. Seismic velocity studies indicate that a paleo-accretionary complex that is sandwiched between the present, relatively small active accretionary prism and the continental crust forms the bulk of the continental margin of southern Central Chile.